Overcoming Factors Inhibiting Students' Interest in Reading Through the Concept of Self Awareness - Khusna Farida Shilviana (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
This study to discuss overcoming factors inhibit reading interest students through concept self awareness. Data collection techniques by interviews. Data analysis techniques by data reduction, data presentation, and drawing conclusions. Reading must do especially for students. However, reading interest several students posgraduate PAI UIN Sunan Kalijaga is still low, because there are several factors that hinder their reading interest, namely: 1) low motivation to read; 2) amount of entertainment in this era makes students more to spend time playing handphone, games and watching TV; 3) sometimes difficult to concentrate. The solution with concept self awareness, namely: 1) we must realize to be able to change from problems; 2) make decisions, for example problem low motivation to read by starting to read from the reading we like, problem the amount of entertainment in this era makes students more to spend time playing cellphone, games and watching TV by we have to prepare a special time to read, problem sometimes difficult to concentrate by we can read in a time / place that is quiet / / comfortable so can concentrate fully without distraction; 3) learn to realize the decision; 4) do it little by little; 5) continuous practice; 6) consistent.